Preparation method of high-performance modified silicon carbide
By using fatty acid glycerides as modifiers in deionized water and combining ultrasonic and heat treatment for curing, the problem of silicon carbide powder dispersion was solved, and the preparation of modified silicon carbide powder with high solid content and low viscosity was achieved. This simplifies the process, reduces energy consumption, is environmentally friendly, and improves ceramic performance.
Patent Information
- Application Number
- CN202511141436.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-12-26
- Estimated Expiration
- 2045-08-15
AI Technical Summary
Existing silicon carbide powder is prone to agglomeration during dispersion, the modification process is complex, requires a strongly alkaline environment, the equipment is highly corrosive, energy consumption is high, and acidic wastewater is generated, which affects the performance of ceramics.
Silicon carbide powder is dispersed in deionized water using a fatty acid glyceride modifier, and then cured by ultrasonic and heat treatment. This avoids a strong alkaline environment, simplifies the process, and reduces energy consumption.
Modified silicon carbide powder with high solid content and low viscosity was prepared, exhibiting good suspension stability, reducing equipment requirements, being environmentally friendly, and improving ceramic performance.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a preparation method of high-performance modified silicon carbide, belonging to the technical field of silicon carbide ceramics. BACKGROUND
[0002] Silicon carbide (SiC) is an important ceramic material, which has excellent properties such as light weight, high strength, high wear resistance, oxidation resistance and high temperature resistance, and is widely used in automotive environmental protection, semiconductors, photovoltaics, 5G communication, national defense and military industry and other fields. Due to the small particle size and high surface energy of silicon carbide powder, agglomeration phenomenon is easy to occur during the preparation of silicon carbide slurry, which affects the density and mechanical strength of silicon carbide ceramics. High solid content, low viscosity and uniform dispersion of ceramic slurry are necessary conditions for producing high-quality silicon carbide ceramics. Surface modification can effectively improve the surface state of silicon carbide powder, and has important influence on improving the dispersion of slurry, solid content and flowability of powder.
[0003] According to the existing literature, Yi Zhongzhou et al. used tetramethylammonium hydroxide as a dispersant to modify silicon carbide powder, and added tetramethylammonium hydroxide directly into the silicon carbide slurry. When the pH of the slurry is close to 12, a silicon carbide slurry with a solid content of 70Vol% can be prepared. Su Xiaohong et al. used a composite modifier made of silane coupling agent, salicylic acid and polyacrylamide to modify silicon carbide powder. At pH=12.5, a silicon carbide slurry with a viscosity of 0.1Pa•s and a solid content of 57Vol% can be prepared. Ji Xiaoli used amino silane coupling agent to modify silicon carbide powder. The modified silicon carbide powder can prepare a slurry with a solid content of 57Vol%.
[0004] It can be seen that after the current modification of silicon carbide powder, the pH of the slurry is in a strong alkaline environment, which requires the equipment to be resistant to strong alkaline environment, and has high requirements on the equipment. At the same time, it affects the forming and firing of the green body, and limits the downstream application.
[0005] The patent application with publication number CN108264360A discloses a preparation method of high-performance silicon carbide modified powder, which uses silicon carbide powder as raw material, and three kinds of modifiers containing hydroxyl carboxylic acid organic matter, tetramethylammonium hydroxide and polyether siloxane to cooperatively modify the silicon carbide powder by a two-step method. However, the modification process is complex and energy-consuming, and an organic silicon dispersant needs to be added additionally, which affects the performance of downstream ceramic structural parts.
[0006] Patent application with publication number CN105884365A discloses a production process of modified silicon carbide ceramic slurry, which specifically comprises the following steps: firstly, silicon carbide powder is pretreated with acid, then separated, washed with water, modified by adding a silane coupling agent, separated, and finally dried to obtain modified silicon carbide powder. The modification process is complex and has high energy consumption. During the pretreatment of silicon carbide, a large amount of acidic wastewater is generated, which has high environmental protection cost. In addition, an organic silicon dispersant needs to be added, which affects the performance of downstream ceramic structural parts.
[0007] Based on the above analysis and combined with actual production, it is found that the prior art of silicon carbide surface modification has the following disadvantages:
[0008] 1) Silicon carbide is prone to agglomeration when dispersed in water, the surface of silicon carbide cannot be completely wrapped by the dispersant, and only physical adsorption is produced between the dispersant and the surface of silicon carbide powder, which is not firm.
[0009] 2) During the modification process and application, the pH of the slurry is strongly alkaline, which is corrosive to the equipment.
[0010] 3) The modification process is complex and has high energy consumption. During the pretreatment of silicon carbide, a large amount of acidic wastewater is generated, which has high environmental protection cost. In addition, an organic silicon dispersant needs to be added, which affects the performance of downstream ceramic structural parts. SUMMARY
[0011] The present application provides a preparation method of high-performance modified silicon carbide, which has low equipment requirements, simple modification process, low energy consumption, does not affect the performance of downstream silicon carbide ceramics, is green and environmentally friendly, and can directly obtain high-quality modified silicon carbide powder with high solid content and low viscosity.
[0012] The technical scheme for solving the above technical problems is as follows: a preparation method of high-performance modified silicon carbide, which comprises the following steps:
[0013] S1, dispersing silicon carbide powder into deionized water, adding a fatty acid glyceride modifier, and mixing uniformly to obtain a silicon carbide slurry;
[0014] S2, ultrasonic treatment, solid-liquid separation, and heat treatment and solidification of the silicon carbide slurry to obtain modified silicon carbide.
[0015] On the basis of the above technical scheme, the present application can also be improved as follows:
[0016] Further, in step S1, the mass ratio of the silicon carbide powder to deionized water is 1: (1-2.5).
[0017] Further, the addition amount of the fatty acid glyceride modifier is 0.1%-1% of the mass of the silicon carbide powder.
[0018] Further, the fatty acid glyceride modifier is at least one of monopalmitic glyceride, diglyceride, monooleic glyceride, dioleic glyceride, monostearic glyceride.
[0019] Further, in step S1, the particle size D50 of the silicon carbide powder is 0.5-10 μm.
[0020] Further, in step S1, after adding the fatty acid glyceride modifier, stirring is carried out at a temperature of 5-60°C for 1-24h at a stirring speed of 200-400r / min to obtain the silicon carbide slurry.
[0021] Further, in step S2, during ultrasonic treatment, the ultrasonic power is 500-5000W, the ultrasonic temperature is 20-60°C, and the ultrasonic time is 30min-2h.
[0022] Further, in step S2, the solid-liquid separation is carried out by centrifugation, and during the centrifugation, the centrifugal speed is 2000-5000r / min, and the centrifugal time is 20min-120min.
[0023] Further, in step S2, the heat treatment solidification process is: 80-120°C for 1-3h, 150-200°C for 1-3h, and 300-350°C for 1-3h.
[0024] Further, during the heat treatment solidification process, the heating speed is 5-10°C / min; after the heat treatment solidification, cooling to room temperature to obtain the modified silicon carbide.
[0025] The beneficial effects of the present application are:
[0026] 1) The preparation method of the present application adopts a stirring modification process instead of a traditional ball milling process, and the process is simple and has low energy consumption.
[0027] 2) The preparation method of the present application adopts ultrasonic treatment combined with heat treatment solidification, and the ultrasonic treatment can effectively break the silicon carbide agglomerates, expose more active surfaces, and promote the adsorption of the modifier; the heat treatment solidification can enhance the bonding force between the dispersant and the surface of the silicon carbide.
[0028] 3) The preparation method of the present application avoids a strong alkaline modification system, and the modification system has a neutral pH, greatly reduces the wastewater treatment cost, is friendly to the environment, and reduces the requirements for equipment.
[0029] 4) The preparation method of the present application avoids adding a dispersant containing silicone, and the prepared modified silicon carbide powder has low silicone content, thereby improving the performance of downstream ceramic products.
[0030] 5) The modified silicon carbide powder prepared by the preparation method has a maximum solid content of 70.1 vol% and an apparent viscosity of less than 50 Pa s. DETAILED DESCRIPTION
[0031] In order to make the above objectives, features and advantages of the present application more apparent, the specific embodiments of the present application are described in detail below. In the following description, a large number of specific details are set forth in order to facilitate a full understanding of the present application. However, the present application can be implemented in many different ways other than the ways described herein, and those skilled in the art can make similar improvements without departing from the scope of the present application, and therefore the present application is not limited to the specific embodiments disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present application belongs. The terminology used in the description of the present application herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application.
[0033] A preparation method of high-performance modified silicon carbide, the preparation method comprises the following steps:
[0034] S1, dispersing silicon carbide powder into deionized water, adding a fatty acid glyceride modifier, and uniformly mixing to obtain a silicon carbide slurry;
[0035] S2, ultrasonic treatment, solid-liquid separation and heat treatment and solidification of the silicon carbide slurry to obtain modified silicon carbide.
[0036] On the basis of the above technical solution, the present application can also be improved as follows:
[0037] Specifically, in step S1, the mass ratio of the silicon carbide powder to the deionized water is 1: (1-2.5).
[0038] Specifically, the fatty acid glyceride modifier is added in an amount of 0.1%-1% of the mass of the silicon carbide powder.
[0039] Specifically, the fatty acid glyceride modifier is at least one of monopalmitate, diglyceride, glycerol monooleate, glycerol dioleate, and glycerol monostearate.
[0040] Specifically, in step S1, the particle size D50 of the silicon carbide powder is 0.5-10 μm.
[0041] Specifically, in step S1, after the fatty acid glyceride modifier is added, stirring is performed at a temperature of 5-60°C for 1-24 h at a stirring speed of 200-400 r / min to obtain the silicon carbide slurry.
[0042] Specifically, in step S2, the ultrasonic time is 30 min to 2 h, the ultrasonic power is 500 to 5000 W, and the ultrasonic temperature is 20 to 60℃.
[0043] Specifically, in step S2, the centrifugal speed is 2000 to 5000 r / min, and the centrifugal time is 20 min to 120 min.
[0044] Specifically, in step S2, the heat treatment solidification process is: 80 to 120℃ for 1 to 3 h, 150 to 200℃ for 1 to 3 h, and 300 to 350℃ for 1 to 3 h.
[0045] Specifically, in the heat treatment solidification process, the heating rate is 5 to 10℃ / min; after heat treatment and solidification, the modified silicon carbide is obtained by cooling to room temperature.
[0046] Example 1
[0047] A preparation method of high-performance modified silicon carbide, the preparation method comprises the following steps:
[0048] 1) The silicon carbide powder and deionized water are mixed according to the mass ratio of 1:1, and a modifier is added. The addition amount of the modifier glycerol monostearate is 0.1% of the mass of the silicon carbide powder, the stirring speed is 300 r / min, and the stirring is carried out at 20℃ for 3 h to obtain a silicon carbide slurry.
[0049] 2) The slurry of step 1) is subjected to ultrasonic treatment at 1000 W for 2 h at 20℃, and then centrifuged at a speed of 5000 r / min for 20 min, and then subjected to heat treatment at 80℃ for 3 h, at 150℃ for 2 h, and at 350℃ for 1 h at a heating rate of 5℃ / min to obtain a modified silicon carbide powder.
[0050] 3) The modified silicon carbide powder is fully dispersed in water to prepare a slurry with a solid content of 53 Vol%, and the apparent viscosity is 26 Pa•s. The maximum solid content can reach 70 Vol%. The slurry has good suspension stability, and no obvious sedimentation phenomenon is observed for the slurry with a solid content of 10 Vol% after standing for 72 h. The pH value is 7.
[0051] Example 2
[0052] A preparation method of high-performance modified silicon carbide, the preparation method comprises the following steps:
[0053] 1) The silicon carbide powder and deionized water are mixed according to the mass ratio of 1:1.5, and a modifier is added. The addition amount of the modifier glycerol monostearate is 0.3% of the mass of the silicon carbide powder, the stirring speed is 200 r / min, and the stirring is carried out at 30℃ for 1 h to obtain a silicon carbide slurry.
[0054] 2) The slurry from step 1) was ultrasonicated at 30°C for 1 hour with a power of 2000W, then centrifuged at 3000r / min for 30 minutes, and kept at 100°C for 2 hours, 200°C for 1 hour, and 350°C for 2 hours with a heating rate of 10°C / min to obtain modified silicon carbide powder.
[0055] 3) Modified silicon carbide powder was fully dispersed in water to prepare a slurry with a solid content of 53 vol%, an apparent viscosity of 34 Pa•s, and a maximum solid content of 69 vol%. It has good suspension stability; a slurry with a solid content of 10 vol% showed no obvious sedimentation after standing for 72 hours, and the pH value was 7.
[0056] Example 3
[0057] A method for preparing high-performance modified silicon carbide, wherein the preparation method comprises:
[0058] 1) Mix silicon carbide powder with deionized water at a mass ratio of 1:2, and add a modifier. The amount of the modifier dioleoglycerate added is 0.8% of the mass of silicon carbide powder. Stir at 400 r / min and 20℃ for 5 h to obtain silicon carbide slurry.
[0059] 2) The slurry from step 1) was ultrasonicated at 4500W power and 60℃ for 30 min, then centrifuged at 4000r / min for 30 min, and kept at 120℃ for 1 h, 200℃ for 2 h, and 350℃ for 1 h at a heating rate of 5℃ / min to obtain modified silicon carbide powder.
[0060] 3) Modified silicon carbide powder was fully dispersed in water to prepare a slurry with a solid content of 53 vol%, an apparent viscosity of 46 Pa•s, and a maximum solid content of 68 vol%. It has good suspension stability; a slurry with a solid content of 10 vol% showed no obvious sedimentation after standing for 72 hours, and the pH value was 7.
[0061] Example 4
[0062] A method for preparing high-performance modified silicon carbide, wherein the preparation method comprises:
[0063] 1) Mix silicon carbide powder with deionized water at a mass ratio of 1:2.5, and add a modifier. The amount of modifier glyceryl monooleate added is 1% of the mass of silicon carbide powder. Stir at 300 r / min and 60℃ for 2 h to obtain silicon carbide slurry.
[0064] 2) The slurry of step 1) is ultrasonically treated at 5000W power for 2h at 25℃, and then centrifuged at 2000r / min for 120min, and then incubated at 80℃ for 3h, at 180℃ for 3h, and at 300℃ for 3h at a temperature increasing rate of 5℃ / min to obtain the modified silicon carbide powder.
[0065] 3) The modified silicon carbide powder is fully dispersed in water to prepare a slurry with a solid content of 53Vol%, and the apparent viscosity is 38 Pa·s, and the maximum solid content can reach 69Vol%. The suspension stability is good, and the slurry with a solid content of 10Vol% does not have obvious sedimentation phenomenon after being static for 72h, and the pH value is 7.
[0066] Example 5
[0067] A preparation method of high-performance modified silicon carbide, the preparation method comprises the following steps:
[0068] 1) Silicon carbide powder and deionized water are mixed according to a mass ratio of 1:2, and a modifier is added. The addition amount of the modifier glycerin diester is 0.5% of the mass of the silicon carbide powder, the stirring speed is 400r / min, and the stirring is performed at 5℃ for 24h to obtain a silicon carbide slurry.
[0069] 2) The slurry of step 1) is ultrasonically treated at 500W power for 1h at 35℃, and then centrifuged at 3000r / min for 60min, and then incubated at 100℃ for 2h, at 180℃ for 3h, and at 350℃ for 2h at a temperature increasing rate of 5℃ / min to obtain the modified silicon carbide powder.
[0070] 3) The modified silicon carbide powder is fully dispersed in water to prepare a slurry with a solid content of 53Vol%, and the apparent viscosity is 42 Pa·s, and the maximum solid content can reach 68Vol%. The suspension stability is good, and the slurry with a solid content of 10Vol% does not have obvious sedimentation phenomenon after being static for 72h, and the pH value is 7.
[0071] Comparative Example 1
[0072] The modified silicon carbide is prepared by the same method as that in Example 1, and the difference is that the ultrasonic treatment is not performed in step 2) of the comparative example 1, and the specific process is as follows:
[0073] 1) Silicon carbide powder and deionized water are mixed according to a mass ratio of 1:1, and a modifier is added. The addition amount of the modifier glycerin diester is 0.1% of the mass of the silicon carbide powder, the stirring speed is 300r / min, and the stirring is performed at 20℃ for 3h to obtain a silicon carbide slurry.
[0074] 2) The slurry of step 1) was centrifuged at 5000 r / min for 20 min, and then was kept at 80℃ for 3 h, 150℃ for 2 h, and 350℃ for 1 h at a heating rate of 5℃ / min to obtain the modified silicon carbide powder.
[0075] 3) The modified silicon carbide powder was fully dispersed in water to prepare a slurry with a solid content of 53 Vol%, an apparent viscosity of 124 Pa·s, and a maximum solid content of 57 Vol%. The suspension stability was poor, and the slurry with a solid content of 10 Vol% settled after being kept still for 72 h, with a pH value of 7.
[0076] As can be seen from the comparison of the experimental results of Comparative Example 1 and Example 1, if the slurry is not subjected to ultrasonic treatment during the preparation of the modified silicon carbide, the silicon carbide particles are prone to agglomeration, and the modifier cannot be completely and effectively adsorbed on the surface of the silicon carbide particles, resulting in an increase in the apparent viscosity of the slurry, a decrease in the maximum solid content, and a settling phenomenon of the slurry after being kept still for 72 h.
[0077] Comparative Example 2
[0078] The modified silicon carbide was prepared by the same method as in Example 1, except that the heat treatment and solidification in step 2) of Comparative Example 2 were not performed, and the specific process was as follows:
[0079] 1) The silicon carbide powder was mixed with deionized water at a mass ratio of 1:1, and a modifier was added. The addition amount of the modifier glycerol monostearate was 0.1% of the mass of the silicon carbide powder, and the stirring speed was 300 r / min. The slurry was stirred at 20℃ for 3 h to obtain a silicon carbide slurry.
[0080] 2) The slurry of step 1) was subjected to ultrasonic treatment at a power of 1000 W and a temperature of 20℃ for 2 h, and then was centrifuged at a speed of 5000 r / min for 20 min. The modified silicon carbide powder was obtained by vacuum drying at 60℃.
[0081] 3) The modified silicon carbide powder was fully dispersed in water to prepare a slurry with a solid content of 53 Vol%, an apparent viscosity of 96 Pa·s, and a maximum solid content of 60 Vol%. The suspension stability was poor, and the slurry with a solid content of 10 Vol% settled after being kept still for 72 h, with a pH value of 7.
[0082] As can be seen from the comparison of the experimental results of Comparative Example 2 and Example 1, if the heat treatment and solidification are not performed during the preparation of the modified silicon carbide, the modifier is not firmly adsorbed on the surface of the silicon carbide, and rapid stirring is required during the preparation of the slurry, resulting in the falling off of part of the modifier, an increase in the apparent viscosity of the slurry, a decrease in the maximum solid content, and a settling phenomenon of the slurry after being kept still for 72 h.
[0083] Comparative Example 3
[0084] The modified silicon carbide was prepared by the same method as in Example 1, except that in step 2) of the present comparative example 3, the heat treatment and curing process was performed at the same temperature throughout, and the process was as follows:
[0085] 1) The silicon carbide powder was mixed with deionized water at a mass ratio of 1:1, and a modifier was added. The amount of the modifier, glycerol monostearate, added was 0.1% of the mass of the silicon carbide powder, and the stirring speed was 300 r / min. The mixture was stirred at 20°C for 3 h to obtain a silicon carbide slurry.
[0086] 2) The slurry of step 1) was subjected to ultrasonic treatment at 1000 W for 2 h at 20°C, and then centrifuged at a speed of 5000 r / min for 20 min. The mixture was heat treated at 350°C for 6 h, with a heating rate of 5°C / min, to obtain a modified silicon carbide powder.
[0087] 3) The modified silicon carbide powder was dispersed in water to prepare a slurry with a solid content of 53 Vol%, and the apparent viscosity was 1726 Pa•s. The maximum solid content was 35 Vol%. The suspension stability was poor, and the slurry with a solid content of 10 Vol% settled after being left still for 72 h. The pH value was 7.
[0088] From the comparison of the experimental results of Comparative Example 3 and Example 1, it can be seen that if the heat treatment and curing process is not performed according to the stepwise heating, the molecular structure of the modifier changes, the modifier is ineffective, the apparent viscosity of the slurry increases, the maximum solid content decreases, and the slurry settles after being left still for 72 h.
[0089] Comparative Example 4
[0090] The modified silicon carbide was prepared by the same method as in Example 1, except that in step 1) of the present comparative example 4, the amount of the modifier was increased, and the process was as follows:
[0091] 1) The silicon carbide powder was mixed with deionized water at a mass ratio of 1:4, and a modifier was added. The amount of the modifier, glycerol monostearate, added was 0.1% of the mass of the silicon carbide powder, and the stirring speed was 300 r / min. The mixture was stirred at 20°C for 3 h to obtain a silicon carbide slurry.
[0092] 2) The slurry of step 1) was subjected to ultrasonic treatment at 1000 W for 2 h at 20°C, and then centrifuged at a speed of 5000 r / min for 20 min. The mixture was heat treated at 80°C for 3 h, 150°C for 2 h, and 350°C for 1 h, with a heating rate of 5°C / min, to obtain a modified silicon carbide powder.
[0093] 3) The modified silicon carbide powder was dispersed in water to prepare a slurry with a solid content of 53 Vol%, an apparent viscosity of 36 Pa-s, and a maximum solid content of 68 Vol%. The slurry with a solid content of 10 Vol% was stable for 72 h without obvious sedimentation, and the pH value was 7.
[0094] From the comparison of the experimental results of Comparative Example 4 and Example 1, it can be seen that if the amount of the prepared modifier is too much, the apparent viscosity and the maximum solid content of the slurry will not be affected, but many air bubbles will appear in the slurry, resulting in cracks on the surface of the ceramic after firing, which affects the bending and compression resistance of the ceramic structural parts.
[0095] Comparative Example 5
[0096] 1) The silicon carbide powder was mixed with deionized water at a mass ratio of 1:1, and a modifier was added. The amount of the modifier, glycerol monostearate, was 0.1% of the mass of the silicon carbide powder. The mass ratio of the ball milling medium to the silicon carbide powder was 2:1, and the slurry was obtained by ball milling at a speed of 200 r / min for 10 h.
[0097] 2) The slurry of step 1) was centrifuged at a speed of 3000 r / min for 30 min, and then dried at a temperature of 80°C for 15 h to obtain the final modified silicon carbide powder.
[0098] 3) The modified silicon carbide powder was dispersed in water to prepare a slurry with a solid content of 53 Vol%, an apparent viscosity of 650 Pa-s, and a maximum solid content of 55 Vol%. The slurry with a solid content of 10 Vol% was stable for 72 h without obvious sedimentation, and the pH value was 7.
[0099] From the comparison of the experimental results of Comparative Example 5 and Example 1, it can be seen that the modification of silicon carbide by ball milling is poor.
[0100] The modified silicon carbide powder prepared in the above examples and comparative examples was made into ceramic products, and the same process was used in the preparation of the ceramic products. The specific process was as follows: the silicon carbide powder (the silicon carbide powder included coarse particle silicon carbide and modified silicon carbide, the mass ratio of the coarse particle silicon carbide and the modified silicon carbide was 1:1.5, the coarse particle silicon carbide was unmodified silicon carbide, the coarse particle included large particle silicon carbide (particle size 50-100 μm) and small particle silicon carbide (particle size 1-5 μm), the mass ratio of the large particle silicon carbide and the small particle silicon carbide was 1:1), a binder and an additive were mixed in a certain proportion, the mass ratio of the silicon carbide powder, the binder and the additive was 1:1%:0.1%, the binder was polyvinyl alcohol (PVA), and the additive was silane coupling agent YDH-560; the mixed material was made into a green body by slip casting, and then was dried and degassed, and finally was sintered at 2100-2300°C. The ceramic products were tested for performance, and the specific test results are shown in Table 1. The specific test methods involved are as follows:
[0101] 1) Density test: determined according to the Archimedes principle by the drainage method.
[0102] 2) Bending strength test: the three-point bending method of a CMT-5105 type microcomputer controlled electronic universal testing machine was used to test the bending strength of ceramic samples with a size of 3×4×36 mm, the test followed the GB6569-86 standard, the span was 20 mm, and the loading rate was 0.5 mm / min.
[0103] 3) Compressive strength test: the CMT-5105 type microcomputer controlled electronic universal testing machine was used to test the compressive strength of ceramic samples with a size of 3×4×36 mm, the span was 20 mm, and the loading rate was 0.5 mm / min.
[0104] Table 1: Performance test results of ceramic products
[0105]
[0106] From the above table data, it can be seen that the ceramic products prepared from the modified silicon carbide of examples 1-5 have better bulk density, bending resistance and compressive strength.
[0107] The comparative analysis of the ceramic products prepared from the modified silicon carbide of comparative example 1 and example 1 shows that:
[0108] In Example 1, the modified silicon carbide is prepared by ultrasonic treatment, which can fully disaggregate the agglomerated silicon carbide particles, and the modifier can be effectively adsorbed on the surface of the silicon carbide particles, so that the prepared slurry has small viscosity and good fluidity, the solid content of the slurry can be greatly increased during injection, and the slurry has good stability, the green body formed has uniform texture and high solid content, so that the sintered ceramic has high density and good bending and compression resistance.
[0109] In Comparative Example 1, the modified silicon carbide is not prepared by ultrasonic treatment, the silicon carbide particles are easily agglomerated, and the modifier cannot be completely and effectively adsorbed on the surface of the silicon carbide particles, resulting in large viscosity and poor fluidity of the slurry, the solid content of the slurry needs to be reduced during injection, and the slurry has poor stability, the green body formed has uneven texture, so that the sintered ceramic has small density and poor bending and compression resistance.
[0110] Comparative Example 2 and Example 1 can be seen from the analysis of the ceramic products prepared by using the modified silicon carbide.
[0111] In Example 1, the modified silicon carbide is prepared by heat treatment and solidification, which can firmly adhere the modifier to the surface of the silicon carbide, so that the modifier is not easily detached from the surface of the silicon carbide during the preparation of the slurry, the prepared slurry has small viscosity and good fluidity, the solid content of the slurry can be greatly increased, the slurry has good stability, the green body formed has uniform texture and high solid content, so that the sintered ceramic has high density and good bending and compression resistance.
[0112] In Comparative Example 2, the modified silicon carbide is not prepared by heat treatment and solidification, which causes part of the modifier to fall off from the surface of the silicon carbide during the preparation of the slurry, resulting in large viscosity and poor fluidity of the slurry, the solid content of the slurry needs to be reduced during injection, and the slurry has poor stability, the green body formed has uneven texture, so that the sintered ceramic has small density and poor bending and compression resistance.
[0113] Comparative Example 3 and Example 1 can be seen from the analysis of the ceramic products prepared by using the modified silicon carbide.
[0114] In Comparative Example 3, the heat treatment and solidification process for preparing the modified silicon carbide is not carried out according to the stepwise temperature rising heat treatment, but is carried out at the same temperature throughout the process, so that the molecular structure of the modifier changes, the modifier is ineffective, the slurry has large viscosity and poor fluidity, the solid content of the slurry needs to be reduced during injection, and the slurry has poor stability, the green body formed has uneven texture, so that the sintered ceramic has small density and poor bending and compression resistance.
[0115] Comparative Example 4 and Example 1 can be seen from the analysis of the ceramic products prepared by using the modified silicon carbide.
[0116] The amount of modifier added in Comparative Example 4 is too much, which does not affect the apparent viscosity of the slurry and the maximum solid content, i.e. the bulk density is not affected, but many bubbles appear in the prepared slurry, and the ceramic surface after firing has defects such as cracking, resulting in poor bending and compression resistance of the sintered ceramic.
[0117] The ceramic products prepared in Comparative Example 5 and Example 1 were compared and analyzed, and it can be seen that:
[0118] Comparative Example 5 uses a ball milling method to modify silicon carbide, which cannot fully disperse the agglomerated silicon carbide, and the adsorption of the modifier on the surface of the silicon carbide is not good, so the ball milling modification cannot reduce the viscosity of the slurry, improve the flowability and solid content of the slurry, and the green body formed has uneven texture, so the sintered ceramic has small density, poor bending and compression resistance.
[0119] The technical features of the above-described embodiments can be combined arbitrarily, and in order to make the description simple, not all possible combinations of the technical features in the above-described embodiments are described, however, as long as the combination of the technical features does not exist contradictory, it should be considered as the scope of the present disclosure.
[0120] The above-described embodiments only express several embodiments of the present application, and the description is more specific and detailed, but it should not be understood as limiting the scope of the patent. It should be pointed out that for ordinary skilled in the art, without departing from the concept of the present application, a number of modifications and improvements can be made, which are within the scope of the present application. Therefore, the scope of protection of the present application should be subject to the appended claims.
Claims
1. A method for producing high-performance modified silicon carbide, characterized by, The preparation method is: S1, the silicon carbide powder is dispersed into deionized water, a fatty acid glyceride modifier is added, and after uniform mixing, a silicon carbide slurry is obtained; the added amount of the fatty acid glyceride modifier is 0.1%-1% of the mass of the silicon carbide powder; the fatty acid glyceride modifier is at least one of monopalmitic glyceride, diglyceride, glycerol monooleate, glycerol dioleate, and glycerol monostearate; S2, the silicon carbide slurry is subjected to ultrasonic treatment, solid-liquid separation, and heat treatment and solidification to obtain modified silicon carbide; In step S2, the heat treatment and solidification process is: 80-120℃ for 1-3h, 150-200℃ for 1-3h, and 300-350℃ for 1-3h; In the heat treatment and solidification process, the heating rate is 5-10℃ / min; After heat treatment and solidification, the modified silicon carbide is obtained after cooling to room temperature.
2. The method of claim 1, wherein the high-performance modified silicon carbide is prepared by the steps of: In step S1, the mass ratio of the silicon carbide powder to deionized water is 1:(1-2.5). 3. The method of claim 1, wherein the high-performance modified silicon carbide is prepared by the steps of: In step S1, the particle size D50 of the silicon carbide powder is 0.5-10μm. 4. The method of claim 1, wherein the high-performance modified silicon carbide is prepared by the steps of: In step S1, after adding the fatty acid glyceride modifier, stirring is performed at a temperature of 5-60℃ for 1-24h at a stirring speed of 200-400r / min to obtain the silicon carbide slurry. 5. The method of claim 1, wherein the high-performance modified silicon carbide is prepared by the steps of: In step S2, during ultrasonic treatment, the ultrasonic power is 500-5000W, the ultrasonic temperature is 20-60℃, and the ultrasonic time is 30min-2h. 6. The method of claim 1, wherein the high-performance modified silicon carbide is prepared by the steps of: In step S2, the solid-liquid separation is performed by centrifugal separation, and during the centrifugal separation, the centrifugal speed is 2000-5000r / min and the centrifugal time is 20min-120min.
Citation Information
Patent Citations
Production technique of modified silicon carbide ceramic slurry
CN105884365A
High-performance silicon carbide modified powder preparation method
CN108264360A
Preparation method of silicon carbide micro powder
CN116854483A
Silicon carbide raw powder for casting and casting method using the same
JP1994144915A